The Students Algebraic Thinking Processed in Mathematic Problem Solving at Low Mathematic Ability Student Based on Quantitative Reasoning Ability - Dewi Purnama Sari; Feny Rita Fiantika (Edumatika : Jurnal Riset Pendidikan Matematika, 2018)
Quantitative Reasoning is the students' ability to concluded a problem solved. The purpose of this research has information about algebraic thinking processed on the student with low ability based on Quantitative Reasoning ability. Methods used qualitative descriptive with a purpose for a description of algebraic thinking processed on mathematics problem solving basic material on function with the low ability of students based on quantitative reasoning ability. This paper used an algebraic ability paper test and interview transcript. The subject cluster used a purposive technic with appreciation high value on report and teacher review which are known about students' characteristics. The results showed that algebraic thinking processed on mathematics problem solving on the student with low ability based on quantitative reasoning ability obtained the less category because the subject doesn’t capable used deductive reasoning on clarifying n symbol on problem and representation on arrow diagram and a Cartesian diagram for the first problem test. With the result that Quantitative Reasoning subject on analyzing problems to extract and quantify essential features with deductive reasoning obtained “Less” category. In the second problem test, the subject doesn’t capable used inductive reasoning on concluding the highest bounce of the ball from the graphic and function table. With that result that Quantitative Reasoning subject to analyzing problems to extract and quantify essential features with inductive reasoning obtained “Less” category.